Ethnoconstructivism analysis: Study of pedagogic mathematics competence of primary school teachers - Syahrial Syahrial; Asrial Asrial; Maison Maison; Amirul Mukminin; Dwi Agus Kurniawan (Institute of Advanced Engineering and Science, 2020)
The teacher has an important role in realizing quality learning. Qualified teachers are shown with good competence. Teacher competency can be improved through teacher understanding of non-constructivism knowledge in mathematics learning. Teachers can integrate cultural values and local wisdom into mathematical concepts to shape student knowledge. Integrating cultural values and local wisdom into mathematics learning makes students learn through their cultural background experiences. This research wasa descriptive research employed 691 respondents. The instruments in this study were questionnaires, tests and interviews to reinforce quantitative results. The purpose of this study was to determine the level of teacher pedagogical knowledge, teacher ethnoconstructivism knowledge, the influence and impact of ethnoconstivism knowledge in mathematics learning. The results of this study indicate the competence of elementary school teachers in Batanghari, Muaro Jambi, and Jambi City tends to be generally not good, and teachers have applied ethno-constructivism in mathematics learning through the use of media, models, and learning strategy. Teachers still encounter many obstacles in the implementation process. And the age range of the teacher has an impact on the level of ethnoconstructivism knowledge in mathematics learning.